TRADISI SUROAN SEBAGAI TAPAK TILAS WALISONGO (STUDI DI DESA JATIREJO KECAMATAN SURUH KABUPATEN SEMARANG) - Damar Safera; Muhammad Chairul Huda (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2020)
Tradition is a pattern of behavior that has deep roots in a society or can be interpreted as a habit that has long been carried out by a certain community in an area, which means carrying out the tradition means also carrying out the process of socialization between generations. Eachs region has a different culture. One of the traditions that is still carried out by the people in Jatirejo Village is the Suroan tradition or commonly called 1 Muharram. The Suroan tradition is a traditional Javanese ceremony in welcoming the Javanese new year which is a cultural assimilation of Javanese culture and Islamic culture carried out by Sultan Agung. People in the village of Jatirejo themselves celebrate it with various forms of activities carried out each year.Suroan tradition which aims to express gratitude to Allah SWT, asking for fortune to be given blessings and gratitude for the harvest and most importantly, so that villagers avoid all kinds of dangers and diseases that afflict or reject. The implementation of the Suroan tradition in the village of Jatirejo, begins with a deliberation between residents and local village officials, then the main event of the Suroan and closing traditions.As for the problem formulation in this study is "how are the economic and religious motives implications in the implementation of the Suroan tradition in the community of Jatirejo Village, Suruh District, Kab. Semarang ".